Natural Silk Development Strategy in East Java Province - Zahrosa, Dimas Bastara; Setiyono, Setiyono; Slameto, Slameto; Prihatin, Jekti; Maharani, Ariq Dewi; Amam, Amam (Faculty of Animal Science, Universitas Brawijaya, 2023)
One of the objectives of regulating the procurement and distribution of silkworm eggs based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.37/MENLHK/SETJEN/KUM.1/6/2017 is to ensure the fulfillment of the need for quality silkworm eggs in sufficient quantities and continuous. The aim of the research is to develop a silkworm business development strategy in East Java Province. The research was conducted using a quantitative descriptive approach. Data collection was carried out using observation methods, Focus Group Discussions (FGD), and surveys. The survey was conducted in 2 ways, namely interviews and filling out questionnaires. Data were analyzed using the Force Field Analysis (FFA) approach, taking into account the driving factors (D) and inhibiting factors (H). The results showed that the main driving factor for the development of the silkworm business in East Java Province was the initiation of silkworm-based educational tourism destinations. On the other hand, the main inhibiting factor was the suboptimal role of the government. The conclusions of the research and policy recommendations based on the consideration of the main driving factors and the main inhibiting factors. The silkworm business development strategy in East Java Province can be implemented by increasing the government's role in formulating policies for the integrated development of silkworm cultivation, aiming for zero waste. This strategy will be complemented by the the concept of educational tourism involving community participation.